Odpowiedzi

2009-12-29T13:55:50+01:00
1)

..=xkwadrat-10x+25-3xkwadrat+3-2xkwadrat+1+2xkwadrat-3x=-2xkwadrat-13x+29

2)..=16-xkwadrat-2x-6xkwadrat+2xkwadrat+8x+8-4xkwadrat+4=
-9xkwadrat+28+6x
2009-12-29T13:57:00+01:00

.1).=xkwadrat-10x+25-3xkwadrat+3-2xkwadrat+1+2xkwadrat-3x=-2xkwadrat-13x+29

2)..=16-xkwadrat-2x-6xkwadrat+2xkwadrat+8x+8-4xkwadrat+4=
-9xkwadrat+28+6x
Najlepsza Odpowiedź!
2009-12-29T14:01:06+01:00
(x-5)²-3(x-1)(x+1)-(2x²-1)+x(2x-3)=x²-10x+25-3(x²-1)-2x²+1+2x²-3x=x²-10x+25-3x²+3-2x²+1+2x²-3x=-2x²-13x+29


(4+x)(4-x)-2x(1-3x)+2(x+2)²-4(x²-1)=16-x²-2x+6x²+2(x²+4x+4)-4x²+4=16-x²-2x+6x²+2x²+8x+8-4x²+4=28+3x²+6x